Air quality and the visitor experience in parks and protected areas. Issue 4 (8th August 2019) - Zajchowski, Chris A. B.; Brownlee, Matthew T. J.; Rose, Jeff
Abstract: Air pollution is one of the greatest environmental health risks facing people worldwide. The transboundary nature of air pollution may place park and protected area (PPA) resources, as well as visitors, at risk of exposure to the same harmful pollutants that plague urban populations. Despite our knowledge of the various impacts of air pollution on endemic species, ecosystem functions, and human health, there exists a gap in our understanding of the affective, behavioral, and cognitive role of air pollution in the visitor experience in PPAs. We reduced this deficit by conducting a scoping review of existing empirical social science literature focused on the social and psychological effects of degraded air quality in and around PPAs. Using a systematic scoping process, we assessed peer-reviewed, empirical social science articles ( n = 458), for evidence of human dimensions of air quality scholarship in International Union for Conservation of Nature (IUCN) protected area sites. Results suggest a relative dearth of peer-reviewed social science scholarship explicitly focused on the visitor experience of air quality in PPAs worldwide. Descriptive analyses illustrate a consolidation of scholarship in specific publications, as well as geographic concentration of scholarship in North American protected areas and IUCN Category II (National Parks). Subsequent inductive analyses yielded five emergent themes—ecosystem services, visitor impacts, transit, measurement of behavior, and variable importance—evident in human dimensions of air quality literature, as well as variety of implications for future human dimensions of air quality scholarship and PPA management.